A heterokaryon instability gene in the Rockefeller-Lindegren strains of Neurospora crassa and its possible relation to the het i gene in Oak Ridge-St. Lawrence strains - J F Wilson; Charles P Calligan; Jo Ann Dempsey (Fungal Genetics Reports, 1999)
The het I/i genes in the Oak Ridge-St. Lawrence (OR-SL) strains of Neurospora crassa are unique among the het genes in that they do not cause cell death in incompatible heterokaryons. Instead, within certain nuclear ratios, forced heterokaryons are unstable. They become homokaryotic for the het I component, and stop growing. Similar alleles have now been found in Rockefeller-Lindegren (RL) strains. The latter differ from those of the OR-SL strains in that the heterokaryons become homokaryotic over a wide range of initial nuclear ratios. Evidence is presented that suggests the two sets of alleles may be the same.